Perilaku Geser Tanah yang Distabilisasi dengan Abu Ampas Tebu-Semen dan Inklusi Serat Polyester - Hatmoko, John Tri; Suryadharma, Hendra (Department of Civil Engineering, Diponegoro University, 2017)
Bagasse ash is a fine residue collected from the burning of bagasse in sugar factory, and it behaves as pozzolanic materials. In addition, engineering behaviour of bagasse ash can be improved by addition of cement containing high calcium. Recently, research about cement stabilized soil is continuously in progress. In this paper, a set of experiment programs were done to investigate the randomly oriented polyester fibre inclusion in bagasse ash-cement stabilized soil. Bagasse ash was mixed with clay in different proportions. To get the optimum curing period, it was done light compaction test of soil with 8% cement cured with 7, 14, 21, 28 and 36 days curing period, that was found on 28 days. The next experiment was compaction test on soil + 8% cement + 3,6,9 and 12% bagasse ash to obtain optimum bagasse ash proportion. The result indicated that optimum bagasse ash content was 9%. To ensure this result, unconfined compression test was done on the same sample. Finally, light compaction, unconfined compression and direct shear tests were done on : soil + 8% cement + 9% bagasse ash + polyester fibre with 28 days curing period. The results showed that maximum dry density and optimum moisture content was not influenced by fibre inclusion, whereas the increase of shear strength of stabilized soil with fibre inclusion was mainly due to improvement of internal friction angle. In unconfined compression test, the unconfined compression strength of stabilized soil was significantly improved by fibre inclusion.